Re-conceptualizing dam design and management for enhanced water and food security - CGIAR Research Program on Water, Land and Ecosystems (International Water Management Institute, 2017)
Dams provide numerous economic benefits and can mitigate the adverse impacts of water variability and extreme climate events. However, such large-scale water infrastructure has also caused significant social and environmental costs, prompting calls for alternative, nature-based solutions. WLE suggests that collections of built and natural infrastructure, combined with participatory management approaches, can support water and food security, while enhancing livelihoods and environmental outcomes.